Produção de celulases pelo FSDE16 e hidrólise enzimática do bagaço de cana-de-açúcar - Cardoso, Amanda Letícia de Carvalho (2017)
With increasing energy demand and pollution problems caused by fossil fuels, lignocellulosic materials have been used as a renewable source of energy in order to minimize environmental problems. Brazil is the largest producer of sugarcane. The enzymes of the cellulolytic system hydrolyze the cellulose present in these materials to fermentable sugars for the production of second-generation ethanol. The pretreatment of the lignocellulosic biomass breaks the lignin shield, reduces the crystallinity of the cellulose and increases its porosity facilitating the enzymatic hydrolysis. The aim of this work was to evaluate the enzymatic hydrolysis of pretreated sugarcane bagasse using enzymes produced by the FSDE16 fungus in the solid-state fermentation. The fungus was cultured in medium containing 60% wheat bran and 40% sugarcane bagasse, enriched with 1% ammonium sulfate solution (m/mH2O). Fermentation was carried out in a 1000 ml erlenmeyer flask containing 100 g of solid medium. The medium was then sterilized and inoculated with a concentration of 106 spores/g. Subsequently, the culture was incubated for 5 days at 33 °C. Afterwards, all fermented was stored under refrigeration for analysis. After that, the study of the best drying temperature of the fermented was carried out, samples of approximately 5 g were dried at temperatures of 50, 60, 70, 80 and 90 °C. Afterwards, the pretreatment of sugarcane bagasse with 3% NaOH (m/v) in 2000mL erlenmeyers at 1:20 solid/solid ratio was performed in autoclave at 121 °C for 90 minutes. And then, the enzymatic hydrolysis of the pretreated bagasse with carried out, considering a 1:20 solid/liquid ratio, under agitation of 150 rpm and a temperature of 50 °C, pH 4.8 and using solid fermented as an enzymatic charge, varying the pretreated/fermented ratio in 1:1, 1:2 and 2:1. The best result of enzymatic activity was at the drying temperature of 60 °C, with a value of 0.09 FPU/mL. For the deactivation of the microorganism, the best result of the drying temperature was 90 °C. For the enzymatic hydrolysis, the best result was for the pre-treated/fermented 1:1 ratio with a peak value of total reducing sugars (ART) of 5.0 g/L in 8 hours, but in relation to the better behavior of the curve of ART, the best result was for the pre-treated/fermented ratio 2:1.